Implementation of Team Games Tournament Learning Model to Improve Science Learning Outcomes - Yuliyanti; Nur Kalifah, Diah Rizki (Jurnal Gentala Pendidikan Dasar, 2025)
The study aims to determine the application of the Team Games Tournament (TGT) learning model to improve the learning outcomes of science subjects on the subject of me and my needs in fourth-grade elementary school students. This study uses a Classroom Action Research (CAR) approach using the Kemmis and Mc. Taggart research design which is carried out through two cycles covering four stages consisting of planning, implementation, observation, and reflection. The research subjects consisted of 18 fourth-grade elementary school students. Data collection techniques used through observation and written tests. Data analysis in this study uses qualitative data analysis, namely with statistical models such as tables and diagrams from the results of observations and values of each cycle and uses quantitative data analysis by comparing data obtained from the implementation of cycle I and cycle II activities. The results of the study indicate that the application of the TGT learning model can improve student learning outcomes in science subjects with an average value of 66.67 in cycle I and obtaining the highest score of 90 with a percentage of 11.1%. in cycle II the average value is 84.44 with the highest score of 100 and a percentage of 22.2%. It can be concluded that the TGT learning model can improve the science learning outcomes of fourth-grade elementary school students.